Impacts of Channel Morphodynamics on Fish Habitat Utilization. - Parsapour-Moghaddam, Parna; Brennan, Colin P.; Rennie, Colin D.; Elvidge, Chris K.; Cooke, Steven J. (Environmental Management, 2019)
It is reasonable to expect that hydro-morphodynamic processes in fluvial systems can affect fish habitat availability, but the impacts of morphological changes in fluvial systems on fish habitat are not well studied. Herein we investigate the impact of morphological development of a cohesive meandering stream on the quality of fish habitat available for juvenile yellow perch (Perca flavescens) and white sucker (Catostomus commersonii). A three-dimensional (3D) morphodynamic model was first developed to simulate the hydro-morphodynamics of the study creek. The results of the morphodynamic model were then incorporated into a fish habitat availability assessment. The 3D hydro-morphodynamic model was successfully calibrated using an intensive acoustic Doppler current profiler (ADCP) spatial survey of the entire 3D velocity field and total station surveys of topographic changes in a meander bend in the study creek. Two fish sampling surveys were carried out at the beginning and the end of the study period to determine presence–absence of fish as an indicator of the habitat utilization of each fish species in the study reach. It was shown that morphological development of the stream was a significant factor for the observed changes in the habitat utilization of juvenile yellow perch. It is shown that juvenile yellow perch mostly utilized habitat where deposition occurred whereas they avoided areas of erosion. The results of this study and the proposed methodology could provide some insights into the potential impact of sediment transport processes on the fish occurrence, and distribution and has implications for management of small fluvial systems.